(untitled) (Research, Society and Development, 2023)
Introduction: The epidemiological profile of HIV prevalence has changed, and there has been an increase in incidence from the age of 50, thus, individuals become more susceptible to the contagion of this infection. Objective: To analyze the scientific evidence regarding the QoL of elderly people living with HIV. Methodology: This is an integrative review, conducted in August and September 2021 at LILACS, MEDLINE, SCIELO, BDENF and PUBMED, through the following guiding question: What is the scientific evidence regarding the quality of life of elderly people with the Human Immunodeficiency Virus (HIV)? The following Health Science Descriptors (DECS) were selected: "Elderly", "HIV", "quality of life", "health education" and "health of the elderly", in English, using the Boolean operator AND. Results: After selecting the articles, the data were categorized into three broad dimensions: (1) Aspects that interfere with mental health in elderly living with HIV according to the QoL domains; (2) Understanding the sexual life and level of independence of the elderly with HIV; (3) The relevance of the role of health professionals in the follow-up of the elderly living with HIV. Final considerations: It is essential for health professionals to know and apply the scales for measuring QoL in PLHIV, in order to subsidize professional practice and support their performance in the dimensions of diminished quality of life.